(untitled) (Journal of Enam Medical College, 2021)
Hirschsprung’s disease (HD) is a rare genetic congenital defect of intestine causing failure of migration of parasympathetic ganglionic cells in some definite part of intestine, resulting in functional intestinal obstruction. It commonly involves rectosigmoid region of colon but other parts of colon or total colon, even small intestine may be affected. Incidence is 1/5000 live births. It is one of the common pediatric surgical problems and 2nd most organic cause of constipation. Symptoms may be evident from 1st day of life. About 90% infants with Hirschprung’s disease fail to pass meconium in 1st 24 hours of life. About 80% HD cases are diagnosed in early few months of life and present with abdominal distention, constipation, poor feeding, vomiting etc. HD enterocolitis is a devastating condition related to mortality. HD may be associated with some congenital anomalies and syndrome. High index of suspicion is the main key to diagnosis. Radiological investigation supports the diagnosis and rectal biopsy for histopathology is confirmatory. Although it is a surgical problem, physician can play a key role in early diagnosis and thus help to prevent HD enterocolitis-related mortality and restore near-normal life. J Enam Med Col 2020; 10(2): 104-113